Śląska okolica - Rosiński, Cezary (Śląskie Studia Polonistyczne, 2013)
Zapisywanie miejsca. Szkice o Śląsku w literaturze przełomu wieków XX i XXI by Elżbieta Dutka is a virgin work devoted to the relationship between a human being and a concrete and real space, it being Silesia. The author focuses on topographies – various ways of inscribing places into the culture, while the place may mean here a concrete localization, phantasmagory, a private homeland or even an internal conception of the author. The researcher is interested in a spacious dimension of human experiences, yet she does not aim at a synthesis of the phenomena observed, but stops at an overview of Silesia in various fields of art and the analysis as well as interpretation of selected works. She bases her discussions on theoretical assumptions by Martin Heidegger, Hanna Buczyńska-Garewicz and Tadeusz Sławek. At the same time, she looks for values that are universal and global in localness, which is not necessarily translatable.